Pre‐transplant cognitive screening is a poor predictor of post‐transplant cognitive status. Issue 11 (31st August 2022) - Gupta, Aditi; Montgomery, Robert N.; Young, Kate; Mukherjee, Rishav; Chakraborty, Shweta; Thomas, Tashra S.; Cibrik, Diane M.; Drew, David; Sarnak, Mark
Abstract: Introduction: Transplant centers hesitate to transplant patients with cognitive impairment. It is unclear if pre‐kidney transplant (KT) cognitive screening can predict post‐KT cognitive function. Methods: We evaluated pre‐ to post‐KT cognitive function with the Montreal Cognitive Assessment (MoCA) in a cohort of 108 patients. We used an adjusted logistic regression model to assess pre‐ to post‐KT changes in cognitive status (continuous variable) and a linear mixed model to assess changes in MoCA scores (categorical variable) pre‐ to post‐ KT. Results: The average pre‐ and post‐KT MoCA scores were 25.3 ± 3.0 and 26.4 ± 2.8, respectively. Final pre‐KT score did not predict post‐KT cognitive status (OR = 1.08; 95% CI: .92–1.26; P  = .35). 32% of the patients with a final pre‐KT score ≥26 had at least one post‐KT score < 26. Conversely, 61% of the patients with a final pre‐KT score < 26 had at least one post KT score ≥26. In the linear mixed model analysis, the final pre‐KT score was associated with a small, clinically insignificant (β = .34; 95% CI: .19–.49; P  < .001) effect on the post‐KT score. Conclusion: A low pre‐KT MoCA score is not a strong independent predictor of post‐KT cognitive function and should not preclude patients from receiving a KT.